Dose–response relationship between light exposure and cycling performance. Issue 7 (14th August 2015) - Knaier, R.; Meister, S.; Aeschbacher, T.; Gemperle, D.; Rossmeissl, A.; Cajochen, C.; Schmidt‐Trucksäss, A.
Abstract : Light has a stimulating effect on physical performance if scheduled according to the chronotype, but dose‐dependent effects on performance have not yet been examined. Three groups of healthy men (25.1 ± 3.1 years) were exposed to light for different durations in a parallel group design before a 40‐min time‐trial. In each group, subjects were exposed to either bright light (BL, 4420 lx) or moderate light (ML, 230 lx) in a randomized order in a crossover design. The durations of light exposure were 120 min prior to and during exercise (2HEX; n = 16), 60 min prior to and during exercise (1HEX; n = 10), or only for 60 min prior to exercise (1H; n = 15). Total work performed during the time‐trial in kJ in the 2HEX group was significantly higher in the BL setting (527 kJ) than in ML (512 kJ) ( P = 0.002), but not in 1HEX (BL: 485 kJ; ML: 498 kJ) or 1H (BL: 519 kJ; ML: 514 kJ) ( P = 0.770; P = 0.485). There was a significant ( P = 0.006) positive dose–response relationship between the duration of light exposure and the work performed over the three doses of light exposure. A long duration light exposure is an effective tool to increase total work in a medium length time‐trial in subjects normalized for their individual chronotype.